Pengujian Kebulatan Hasil Pembubutan Poros Aluminium Pada Lathe Machine Type LZ 350 Menggunakan Alat Ukur Roundness Tester Machine - Arief, Dodi Sofyan; Saputra, Rachman; Prayitno, Adhy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Machining process is a manufacturing process in which the object is formed by removing or abolishing most of the material of the object works. Reason used machining process is to obtain accuracy than other processes such as casting process, forming and also to provide a form of the inside of a particular object. This study aimed to obtain the test roundness data of the aluminum shaft using Roundness Tester Machine, process and analyze the test data. This test method 10 points in each axis. The three feeding is used (0.082 mm / rev, 0.114 mm / rev, 0.143 mm / rev) data obtained unanimity the most good at feeding 0.114 mm / rev that is Minimum circumscribed circle 0.045 to 0.229, the Maximum inscribed circle 0,046 to 0,249, Minimum radial zone 0.052 to 0.237, Least Squares Circles 0,024 to 0.134. Based on research data using a lathe turning type LZ 350 Lathe better roundness deviation is second with a feeding shaft 0.114 mm / rev net by a correction factor Roundness Tester Machine is between 0.018 mm to 0.133 mm and the average value of 0.058 mm. The test results obtained are not in accordance with the theory of reference, it should be feeding the lowest (0.082) which has a roundness deviation which was better than feeding 0.114 and 0.143, this can be due to (Humman error) operators put the test center axis or not alignemnt, specify datum turning and lathes Lathe LZ 350 type is not in optimal performance.Keywords: Machining, Roundness, Roundness Tester Machine